Web series “Tiba-Tiba NgeGUIDE” As a Media Promotion for Tourist Destination in Jakarta - Tetta Riyani Valentia (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
Film-induced tourism refers to the phenomenon of people visiting places because they were featured in popular movies or TV shows. The power of cinema to inspire travel has been recognized by the tourism industry for many years, and it has become a significant source of income for many destinations around the world. The concept of film-induced tourism has gained momentum with the rise of social media and the internet, which have made it easier for travelers to research and plan their trips based on the locations they have seen on screen. The impact of film-induced tourism can be significant for both the destinations and the film industry. For destinations, it can create jobs, boost local businesses, and promote the local culture and heritage. For the film industry, it can generate additional revenue and increase exposure for their productions. The concept of film-induced tourism has gained momentum with the rise of social media and the internet, which makes it easier for travelers to research and plan their trips based on the locations they have seen on screens. This is what the Tourism and Creative Economy Service is trying to take advantage of by launching the web series 'Tiba-Tiba NgeGUIDE'. There are two main factors that are discussed in depth, namely the process of making films including pre- production, production and post-production and also the web series itself which is a medium for promoting Jakarta tourism. Literature study, observation, and documentation try to be optimized to collect the required data. In conclusion, the web series Tiba-Tiba NgeGUIDE has succeeded in becoming a media/tool that promotes Jakarta tourism and increases audience awareness of Jakarta's tourist destinations.